Measurement of the inclusive electron cross-section from heavy-flavour decays and search for compressed supersymmetric scenarios with the ATLAS experiment - Backes, Moritz (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
The first part of this thesis presents the measurement of the inclusive cross-section for electron production from heavy-flavour decays in the electron transverse momentum range 7 GeV < pT < 26 GeV using 1.3 pb−1 of 7 TeV proton-proton collision data collected by the ATLAS experiment at the Large Hadron Collider in 2010. The measured value of the cross-section within the fiducial range of the analysis is σ_e^HF = 0.946 ± 0.020(stat.) ± 0.146(syst.) ± 0.032(lumi.) μb. Theoretical predictions are in good agreement with the measurement. The second part of this thesis is a search for compressed supersymmetric scenarios in events with missing transverse energy, jets, and one isolated low-pT lepton in the final state using 4.7 fb-1 of ATLAS data collected at 7 TeV center-of-mass energy in 2011. No significant excess of events over the Standard Model expectation is observed and exclusion limits are derived for a number of supersymmetric models.